(untitled) (mathematica didactica, 2012)
In the present article, the role of multiple solution methods for the development of modelling competency of ninth graders concerning the topic of linear functions will be analysed. To this end, 630 answers of students were categorized and connected with the students` learning progress. The study showed that (1) the students used a wide spectrum of solution methods, (2) progress can be achieved even by a short teaching unit on mathematical modelling, and (3) this progress can be attributed also to the use of a non-formal, contentbased solution method.